2-Hydroxy-5-nitrobenzaldehyde thiosemicarbazone - Alhadi, Abeer A.; Ali, Hapipah Mohd; Puvaneswary, Subramaniam; Robinson, Ward T.; Ng, Seik Weng (International Union of Crystallography, 2008)
The molecule of the title compound, C8H8N4O3S, is planar. Adjacent molecules are linked through O—H⋯S, N—H⋯S and N—H⋯O hydrogen bonds into a three-dimensional network.